Controlled growth of vertically aligned carbon nanotubes from palm oil precursor using thermal chemical vapour deposition method and its field electron emission properties / Suriani Abu Bakar - Abu Bakar, Suriani (Institute of Graduate Studies, UiTM, 2012)
Vertically aligned carbon nanotubes (VACNT) were synthesized using palm oil as an environmentally friendly starting material. The synthesis was carried out in a thermal chemical vapour deposition reactor. Parametric studies were done to determine the optimum parameters to obtain VACNT with favourable properties at high volume. The parameters included seeded and floated catalyst preparation method, stacking substrate configuration (lower and upper growth), synthesis temperature (700- 900°C), palm oil vaporization temperature (300-600°C), synthesis time (5-90 min), different carbon precursor (palm oil and waste cooking palm oil), substrate positioning (position 1-6), ferrocene concentration (0.67-5.33 wt%) and different carrier gas (argon and nitrogen). The carbon nanotubes (CNT) products were then characterized using several analytical techniques which were electron microscopy, energy dispersive x-ray analysis, micro- Raman and Fourier transform infrared (FTIR) spectroscopy, thermogravimetry analysis (TGA) and CHNS-O analysis. Prior to the synthesis process, several analyses such as TGA, gas chromatography–mass spectrometry and FTIR characterizations were done on the carbon precursor namely palm oil and waste cooking palm oil in order to facilitate the optimization procedures of VACNT. For every synthesis parameter, the nanotubes growth rates were measured and the nucleation as well as termination factor were investigated.